2022
DOI: 10.1128/mbio.02819-22
|View full text |Cite
|
Sign up to set email alerts
|

The ESX-1 Substrate PPE68 Has a Key Function in ESX-1-Mediated Secretion in Mycobacterium marinum

Abstract: Pathogenic mycobacteria, such Mycobacterium tuberculosis and Mycobacterium marinum , use a type VII secretion system (T7SS) subtype, called ESX-1, to mediate intracellular survival via phagosomal rupture and subsequent translocation of the mycobacterium to the host cytosol. Identifying the ESX-1 substrate that is responsible for this process is problematic because of the intricate network of codependent secretion between ESX-1 substrates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 80 publications
3
6
0
Order By: Relevance
“…From this, we conclude that the PE/PPE pairs of the esx-5 locus are important for the secretion of the Esx substrates and at least one other PPE protein. This is in line with a recent observation for ESX-1 in M. marinum , where secretion of EsxA is dependent on the co-secretion of PPE68 encoded by the same gene cluster ( 34 , 35 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…From this, we conclude that the PE/PPE pairs of the esx-5 locus are important for the secretion of the Esx substrates and at least one other PPE protein. This is in line with a recent observation for ESX-1 in M. marinum , where secretion of EsxA is dependent on the co-secretion of PPE68 encoded by the same gene cluster ( 34 , 35 ).…”
Section: Resultssupporting
confidence: 93%
“…In addition, we showed that secretion of the Esx heterodimers by ESX-5 is dependent on the locus-encoded PE/PPE proteins. This is in line with a recent observation for ESX-1 in Mycobacterium marinum , where secretion of EsxA is dependent on the co-secretion of PPE68 that is encoded by the same gene cluster ( 34 , 35 ). Notably, PPE68 was observed to be degraded on the cell surface upon export.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, how EsxAB, EsxGH and other substrates and components of the ESX secretion system interact during cell wall transport remains to be further explored. Nevertheless, we note that recent data on ESX-1 suggest a hierarchical model in which, rather than being shuttled or channeled through the cell wall, substrates such as EsxB support their own export out of the cell 55,64 and our data lend additional credence to this model. In summary protein tagging by APEX2 offers unprecedented accuracy in localizing proteins to subcellular compartments of M. tuberculosis, including the cell wall.…”
Section: Discussionsupporting
confidence: 79%
“…These analyses confidently identified a total of 1354 expressed proteins, including several proteins of the ESX-1, ESX-2 and ESX-5 secretion systems (Table S6). ESX-1 substrates and components detected included the major secreted M. tuberculosis antigen CFP-10 (F6B93_22245), the chaperone EspB (F6B93_22290), the PE protein chaperone EspG1 (F6B93_22210) and the ESX-1 secretion regulator EspI (F6B93_22255) (5457). The ESX-5 secretion system has been shown to be essential to slow growing mycobacteria (51, 58) and several substrates of this system were detected, including a full-length version of the substrate EsxM (F6B93_11055), which has been suggested to promote dissemination in ancestral M. tuberculosis lineages (59).…”
Section: Resultsmentioning
confidence: 99%